Disiplin Pegawai Kitchen di Nichi Izakaya Bandung - Heri Sutardi; Bryan Ericko (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the effects of servant leadership and spiritual service quality on organizational engagement through the mediating role of sense of belonging in faith-based communities. Employing an explanatory quantitative design, data were collected from 215 active members of a parish-level faith community through purposive sampling using a five-point Likert scale questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 7.0. Results reveal that spiritual service quality significantly predicts both sense of belonging (β = 0.689, p < 0.001) and organizational engagement (β = 0.145, p = 0.015), while sense of belonging is a strong predictor of organizational engagement (β = 0.649, p < 0.001). Sense of belonging fully mediates the pathway from spiritual service quality to organizational engagement (β_indirect = 0.447, p < 0.001), but does not mediate the servant leadership pathway significantly. Servant leadership shows no direct or significant indirect influence on engagement. The model demonstrates substantial explanatory power (R² = 0.599; GoF = 0.595). The findings underscore that in value-based organizations, spiritual experience quality and psychological belonging are more decisive drivers of engagement than formal leadership structures. Implications for organizational management theory and practice in faith-based settings are discussed.